E-module design based on Golabz for online physics learning about RLC series circuits - Karina Indra Dewi; Debora Natalia Sudjito; Alvama Pattiserlihun (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2022)
There are many virtual physics laboratory applications, i.e., Golabz and Crocodile Physics. This study aims to design online physics learning about RLC series circuits using Golabz, which integrates Crocodile Physics and investigates its effectivity on students' understanding. The research method used here is the development research with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The online physics learning design based on an inquiry about the RLC series circuit using Golabz consists of three learning activities according to the learning objectives. Each learning has five steps, i.e., orientation, conceptualization, investigation, discussion, and conclusion. The research instruments are an observation sheet, evaluation, questionnaire, and validation sheet for the material and media. Based on the research above, the results of learning observation indicate that all respondents can follow the learning well with an average of 82% and gave positive responses to at least 70% of the statements with an average of 98%; some students were able to obtain evaluation results of more than 70% with an average of 71.88%. Thus, all indicators of success are achieved, and the online physics learning design about RLCseries circuits using Golabz is said to be sufficient to help students understand the material of RLC series circuits.